Effect of theaflavin-3,3′-digallate on leptin-deficient induced nonalcoholic fatty liver disease might be related to lipid metabolism regulated by the Fads1/PPARδ/Fabp4 axis and gut microbiota - Zhou, Cheng; Zhang, Wenji; Lin, Hui; Zhang, Luyun; Wu, Fan; Wang, Yan; Yu, Susu; Peng, Xinyue; Cheng, Wenli; Li, Min; Pan, Xiaoying; Huang, Zhenrui; et al. (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD), one of the risk factors for hepatitis, cirrhosis and even hepatic carcinoma, has been a global public health problem. The polyphenol compound theaflavin-3,3'-digallate (TF3), mainly extracted from black tea, has been reported to produce an effect on hypoglycemic and anti-lipid deposition in vitro. In our study, we further investigated the function and the novel mechanisms of TF3 in protecting NAFLD in vivo. By using the leptin-deficient obese (ob/ob) mice with NAFLD symptom, TF3 treatment prevented body weight and waistline gain, reduced the lipid accumulation and alleviated liver function injury, as well as decreased the levels of serum lipid in ob/ob mice, without any side effects. Furthermore, the transcriptome sequencing of liver tissue showed that TF3 treatment corrected the expression profiles of livers in ob/ob mice compared with that of model group, especially by regulating lipid metabolism via Fads1/PPARδ/Fabp4 axis. In addition, intestinal microbial diversity analysis using 16S rRNA sequencing demonstrated that TF3 increased the abundance of Prevotellaceae_UCG-001, norank_f_Ruminococcaceae and GCA-900066575 and significantly decreased that of Parvibacter. The correlation analysis showed that TF3 may regulate lipid metabolism and gut microbiota composition through gut-liver axis to attenuate NAFLD. Taken together, TF3 would be a promising candidate for NAFLD therapy.